Book review: Forgotten children: addressing the health needs of looked after children and young people. The Residential Care Health Project, Astron, Edinburgh - Judy Furnivall (Scottish Journal of Residential Child Care)
Forgotten Children is the report of the Lothian-based Residential Care Health Project. It should be compulsory reading for any health and social work professional who works with looked after and accommodated children. At a simple level, it adds further confirmation of the serious health difficulties facing young people looked after away from their families. The team discovered high levels of psychological and physical morbidity – much of which had either not been diagnosed before or had been lost to follow up because of the lack of stability in children's lives.